Data-Seeking Behaviour in the Social Sciences - Thomas Krämer; Andrea Papenmeier; Zeljko Carevic; Dagmar Kern; Brigitte Mathiak (International Journal on Digital Libraries, 2021)
Purpose Publishing research data for reuse has become good practice in recent years. However, not much is known on how researchers actually find said data. In this exploratory study, we observe the information-seeking behaviour of social scientists searching for research data to reveal impediments and identify opportunities for data search infrastructure.Methods We asked 12 participants to search for research data and observed them in their natural environment. The sessions were recorded. Afterwards, we conducted semi-structured interviews to get a thorough understanding of their way of searching. From the recordings, we extracted the interaction behaviour of the participants and analysed the spoken words both during the search task and the interview by creating affinity diagrams.Results We found that literature search is more closely intertwined with dataset search than previous literature suggests. Both the search itself and the relevance assessment are very complex, and many different strategies are employed, including the creatively “misuse” of existing tools, since no appropriate tools exist or are unknown to the participants.Conclusion Many of the issues we found relate directly or indirectly to the application of the FAIR principles, but some, like a greater need for dataset search literacy, go beyond that. Both infrastructure and tools offered for dataset search could be tailored more tightly to the observed work processes, particularly by offering more interconnectivity between datasets, literature, and other relevant materials.
Keywords: 000; Data search; Dataset retrieval; Social science; User behaviour; User study; Information-seeking behaviour